Echocardiographic features in infants with dilated cardiomyopathy treated with reversible pulmonary banding: a preliminary single-centre experience - Alicja Mirecka-Rola; Monika Kowalczyk-Domagała; Anna Brodzikowska-Pytel; Andrzej Kansy; Grażyna Brzezińska-Rajszys; Lidia Ziółkowska (Termedia Publishing House, 2023)
Reversible pulmonary artery banding (rPAB) was proposed as an innovative therapy for young children with end-stage heart failure due to dilated cardiomyopathy (DCM). We report our early experience with rPAB in 2 infants with DCM and preserved right ventricle (RV) function to evaluate the effectiveness of this treatment. Pre- and postoperative echocardiography included standard evaluation of right (RV) and left (LV) ventricle global systolic function. Moreover, we applied the LV global longitudinal strain for better analysis of LV systolic function. During 15 months of follow-up, clinical and echocardiographic improvement was observed. Our early experience indicates that rPAB may be an effective alternative to heart transplantation or recovery in selected children with DCM.